Analysis of Legal Compliance in the Driving License Issuance Process at the Sragen Police, Central Java - Hasna Ayu Puspita Sari; Sri Waljinah (Proceeding International Conference Restructuring and Transforming Law, 2026)
This study aims to analyze the level of public legal compliance in the process of obtaining a Driver's License (SIM) at the Sragen Police Resort, Central Java. The findings indicate that the level of compliance is still relatively low, reflected in 12,456 cases of drivers without a driver's license in 2025, or approximately 28% of the total results of raids. This condition is influenced by procedures that are considered complicated, the practice of extortion ranging from Rp50,000-Rp200,000, and a lack of service transparency, which indirectly contribute to the occurrence of traffic accidents. This study uses a descriptive qualitative approach with a legal sociology perspective through a case study at the Sragen Police Resort Satpas from February to March 2026. Primary data were obtained through interviews, questionnaires distributed using purposive and total sampling techniques, and field observations for five days. Secondary data are sourced from laws and regulations and related documents. Data analysis was carried out using triangulation techniques using the theoretical framework of Soerjono Soekanto, Lawrence Friedman's legal rationality, Max Weber's legitimacy, and Everett M. Rogers' diffusion of innovation. In contrast to previous research which tends to be normative or have a general focus, this research emphasizes an empirical approach that is specific to the Sragen region and integrates the SERVQUAL concept to identify gaps between law in books and law in action.The research findings indicate that legal substance, law enforcement officers, and the public are still influenced by the practice of extortion, but this can be improved through service innovations such as the Sidora-Polisi Menyapa program, which can reduce service time by up to 60 minutes. This study recommends the need for reform through service digitization, strengthening officer integrity oversight, and increasing public outreach to achieve transparent and accountable public services and reduce traffic accidents.